Evaluation of the legal periodical collections of selected law school libraries in Metro Manila a follow-up study - Oblefias, Chantelle M. (2005)
One way of improving the field of librarianship and library service is to keep track of the improvement and impacts of previous researches through follow-up studies. Journals are one of the most important publication in any field of knowledge for it serves as a tool for providing up to date findings and developments particularly the dynamic field of law.